When do governments "go dark"? Evidence on governments' disclosure choices in periods of uncertainty - Columbano, Claudio; Trombetta, Marco (Taylor & Francis, 2022)
We examine the effect of uncertainty shocks on the level of fiscal guidance – the guidance issued by governments on the expected evolution of the fiscal and economic outlook. Because uncertainty makes governments’ expectations less precise but potentially more valuable to users, we hypothesize that a disclosure dilemma leads governments to balance a higher demand for guidance with a higher probability of issuing inaccurate forecasts. Using natural disasters to randomize uncertainty shocks in our sample, we find that on average, governments issue less guidance in periods of uncertainty. The effect is driven by a reduction in the number of forecasts on the future evolution of balance sheet items, but only when governments have low refinancing needs and face a relatively quiet bond market. Instead, governments that maintain a stable level of guidance in periods of uncertainty appear to cater to coercive isomorphic pressures stemming from creditors. We further document that the relative ‘transparency’ of governments in periods of uncertainty is negatively related to indicators of fiscal reporting quality. Collectively, the evidence indicates that in the public sector, uncertainty leads to a trade-off between disclosure quantity and quality.
Keywords: Government;Uncertainty;Accountability;Transparency;Stability and Growth Pact; Government; Uncertainty; Accountability; Transparency; Stability and Growth Pact; 59 Ciencia Política::5909 Administración pública; ODS 11 - Ciudades y comunidades sostenibles; ODS 16 - Paz, justicia e instituciones sólidas